Rising damp study in UiTM Perak's accommodation : a pilot study / Zaimah Zainal Abidin, Nur Azfahani Ahmad and Alia Abdullah Salleh - Zainal Abidin, Zaimah; Ahmad, Nur Azfahani; Abdullah Salleh, Alia (2019)
Building defects are critical as they can physically affect the building appearance as well as damage the building structure. This can subsequently affect the safety of the building users. Therefore, appropriate solutions to mitigate building defects in academic buildings should be carried out in order to ensure the buildings do not easily fall into defect. If the defects were not taken seriously, it may consequently lead to structural failure. There are many types of dampness that will contribute towards defect as for example rising damp, falling damp and penetrating damp. However, this research focus only on single type of dampness defect, namely rising damp. The aim for this study is to identify the level of rising damp defects and to identify the main contributing factors of humidity defects. Particularly, for rising damp issues happened in the student's accommodation in University Technology Mara (UiTM), Seri Iskandar, Perak. Methods that were used for this research are observations and also by using tools namely Thermal Imager for field work. For this study, I look at the kind of humidity that often occurs in student accommodation. Where the moisture that is always valid and was found in student accommodation will be taken to a more detailed study. Moreover, it also can minimize the number of this type of defects. Results from pilot study that contributed for future researchers to identify and survey details about defects on the buildings at UiTM Perak accommodation and given the many information about the dampness and humidity currently happens at the accommodation. Besides that, it's also can help the management of the building as a guideline to prevent from humidity defects such as rising damp happens to the building. Moreover, it also can minimize the number of this type of defects, humidity and dampness. In addition, by using this tool also, it can provide an accurate result for any findings of study. The findings that have been found by any researcher is important to make any peoples understood. By using thermal imager also, all peoples can save their time to think about any problems that are related to reports, analyse and document the findings. It is because, with this tool, it becomes easy to manage this process and then insert it into any software without any problems.